Treating Rural Water without Introducing Harmful Substances - Ogedengbe, O. (Faculty of Agriculture, University of Ife, 2015)
The coliform count on the stream water studied was high. The water is a direct source of drinking water to some rural communities. A previous study established that about 100 ppm of chlorine in the form of chlorox was sufficient to bring: the coliform Most Probable Number (MPN) from about 11,000 per l00ml down to within allowable standard of one per l00ml of water sample. There is some concern that turbid water contains organic matter which when chlorinated could give rise to formation of chloroform and possibly other chlorine-based compounds of the trihalomethane family which conceivably could be carcinogenic. This prompted design and construction of a simple system of turbidity removal and chlorination. With this system the required chlorine dosage even went down to about -50 ppm.